2016
DOI: 10.1128/msphere.00055-15
|View full text |Cite
|
Sign up to set email alerts
|

Uropathogenic Escherichia coli Metabolite-Dependent Quiescence and Persistence May Explain Antibiotic Tolerance during Urinary Tract Infection

Abstract: Recurrent urinary tract infections (UTIs) affect 10 to 40% of women. In up to 77% of those cases, the recurrent infections are caused by the same uropathogenic E. coli (UPEC) strain that caused the initial infection. Upon infection of urothelial transitional cells in the bladder, UPEC appear to enter a nongrowing quiescent intracellular state that is thought to serve as a reservoir responsible for recurrent UTIs. Here, we report that many UPEC strains enter a quiescent state when ≤106 CFU are seeded on glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 55 publications
3
33
0
Order By: Relevance
“…Some other STs identified in this study are infrequently associated with UPEC, including ST10, ST12, and ST14, (Banerjee et al, 2013a ; Nichols et al, 2016 ), and ST141 (Toval et al, 2014 ; Leatham-Jensen et al, 2016 ). ST141 has also been identified in the fecal flora of healthy individuals (Leflon-Guibout et al, 2008 ).…”
Section: Discussionmentioning
confidence: 61%
“…Some other STs identified in this study are infrequently associated with UPEC, including ST10, ST12, and ST14, (Banerjee et al, 2013a ; Nichols et al, 2016 ), and ST141 (Toval et al, 2014 ; Leatham-Jensen et al, 2016 ). ST141 has also been identified in the fecal flora of healthy individuals (Leflon-Guibout et al, 2008 ).…”
Section: Discussionmentioning
confidence: 61%
“…Indeed, the death of the superficial epithelium is intentionally induced by certain virulent UPEC to better reach deeper tissue where intermediate BECs are located and where they form QIRs and where they can persist for extended period of time. Actually, one of the main reason for high rate recurrence of infections in the bladder and resistance to antibiotics is associated to the presence of QIRs within subepithelium (Leatham-Jensen et al, 2016 ).…”
Section: The Bladder Epithelium Shows Self-defense Mechanisms Againstmentioning
confidence: 99%
“…The renewed scrutiny has now crucially shown that bacterial persistence to antibiotics can lead directly to antibiotic resistance [ 9 , 10 , 11 , 12 ]. This is of great importance since bacterial persisters have been found to cause recalcitrant clinical infections [ 13 , 14 , 15 , 16 , 17 , 18 ]. Nonetheless, early work implicating membrane transport in bacterial persistence to antibiotics [ 19 ] has not attracted the same level of attention.…”
Section: Introductionmentioning
confidence: 99%